2012
DOI: 10.1002/app.37762
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility evaluation of glycolide‐containing polyesters in contact with osteoblasts and fibroblasts

Abstract: Biodegradable aliphatic polyesters have numerous biomedical applications and their capacity to degrade in biological fluids provides the significant advantage of their removal. Three glycolide-containing aliphatic polyesters: a copolymer of glycolide and L-lactide (PGLA), a terpolymer of glycolide, L-lactide and e-caprolactone (PGLCap) and a copolymer of glycolide, and e-caprolactone (PGCap) were tested to evaluate their biocompatibility towards osteoblasts and fibroblasts. Each of the polymer units was previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…PLG proves to be biocompatible, but PLGC reduces the adhesion of all cell types and enhances the activation of macrophages. This undesired effect is attributed to the presence of ε-caprolactone units that endow the polymers with low polarity and higher deformability [30,35]. In our present study, PET-PLG and -PLGC were seeded with bovine EC and, consistently with the previous tests, the lowest EC proliferation occurred on PET-PLGC ( Figure 2C) even when modified with ECM proteins (Figure 3B and 3E).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…PLG proves to be biocompatible, but PLGC reduces the adhesion of all cell types and enhances the activation of macrophages. This undesired effect is attributed to the presence of ε-caprolactone units that endow the polymers with low polarity and higher deformability [30,35]. In our present study, PET-PLG and -PLGC were seeded with bovine EC and, consistently with the previous tests, the lowest EC proliferation occurred on PET-PLGC ( Figure 2C) even when modified with ECM proteins (Figure 3B and 3E).…”
Section: Discussionsupporting
confidence: 84%
“…PLG and PLGC were dissolved in methylene chloride (POCh, Gliwice, Poland) at a concentration of 5% (w/v). The detailed characteristics of PLG and PLGC processed in the form of foils by solvent casting can be found elsewhere [30,35]. These characteristics included: composition, molecular weights, thermal properties, surface chemical composition, contact angles, Surface Free Energies (SFEs), surface topography and average roughness (R a ) as well as mechanical properties in a tensile test.…”
Section: Impregnation Of Vascular Prostheses With Copolymersmentioning
confidence: 99%
“…However, when compared to TCPS, the proliferation ratio of fibroblasts cultured on these scaffolds was significantly decreased [36]. Studies performed previously by our group showed that PLGA processed into form foils stimulated the typical functions of L929 fibroblasts [26,27,37] and did not induce the release of proinflammatory cytokines from macrophages [29]. Moreover, PLGA foils were found to degrade almost completely after 30 weeks of implantation into rat skeletal muscle [32].…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies, we performed in vitro and in vivo analyses of several resorbable aliphatic polyesters containing L-lactide, glycolide, ε-caprolactone and trimethylene carbonate with the aim of using them in bone tissue engineering [24][25][26][27]. All of our materials were synthesized with the use of a biocompatible initiator (zirconium (IV) acetylacetonate), in contrast to typically applied tin compounds [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the shape memory characteristic, the terpolymers based on PLGA and TMC are biocompatible and bioresorbable polymers, which makes them more valuable materials as medical implants. The biocompatibility and biodegradability were confirmed by authoritative in vitro and in vivo studies [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In vitro tests on human chondrocytes settled on the PLLAGATMC matrix confirmed its biocompatibility before and after the degradation process, which lasted 90 days, and there was 7.4% mass loss.…”
Section: Introductionmentioning
confidence: 89%